Examining the Intervention of Religion in Indian Politics Through Hindutva Under the Modi Regime - Vineeth Thomas; Chandana Deka; Aparajitha Raja; Arsha V Sathyan (Religions)
This review article analyses the wide-ranging influence of Hindutva in Indian politics over the decade of Narendra Modi’s tenure as Prime Minister of India. The study analyses the survival, reproduction, and development of Hindutva in conflict with modernisation processes in India despite the country’s secular constitutional democracy. This is achieved by examining the developments in the Indian political landscape and policy administration through the prism of the symbiotic relationship between the Rashtriya Swayamsevak Sangh (RSS) and Bharatiya Janata Party (BJP), signalling the fusion of political power and Hindu religious principles. By contributing to the literature on religion and politics, through a comprehensive examination of political rhetoric, policy shifts, and societal attitudes, this review article examines the role of Hindutva in shaping the trajectory of governance and politics in India during Narendra Modi’s leadership.